Odpowiedzi

  • lmyk
  • Początkujący
2010-01-07T19:51:09+01:00
A) 2(u-5)+15=3(u-4)
2u-10+15=3u-12
2u-3u=10-15-12
-u=-17
u=17
b)-3(y/3+1)-2=4(1-y)
-y-3-2=4-4y
4y-y=4+3+2
3y=9
y=3
c) 2(3a-2)-6=4,5(2a-1)+1/2
6a-4-6=9a-4,5+1/2
6a-9a=4+6-4,5+0,5
-3a=6
3a=-6
a=-2
d)2x-1/2(3x-2)=7/4-x
2x-1,5x+1=1,75-x
2x-1,5x+x=1,75-1
1,5x=0,75
x=0,5
Najlepsza Odpowiedź!
2010-01-07T19:54:37+01:00
A) 2(u-5)+ 15=3(u-4)+10
2u-10+15=3u-12+10
-u= -7
u=7
b)-3(y/3+1)-2=4(1-y)
-y-3-2=4-4y
3y=9
y=3
c) 2(3a-2)-6=4,5(2a-1)+1/2
6a-4-6=9a-4.5+½
-3a=6
a=-2
d) 2x-1/2(3x-2)=7/4-x
2x-1.5x+1=7/4-x
1.5x=0.75
x=0,5